Трансформація вітчизняної економіки: обліково-аналітичний аспект - Ілляшенко, Катерина Володимирівна; Илляшенко, Екатерина Владимировна; Illiashenko, Kateryna (My University, 2019)
UK: У дослідженні розглянуті історичні аспекти інноваційної економіки та етапи її сучасної трансформації. Висвітлені та суб’єктивні передумови переходу від індустріальної економіки до економіки знань. Проаналізовано поняття ролі, місця та характеру функціонування знань. Зазначено, що знання є найбільш важливим і визначальним фактором сучасної економіки. Виділені основні умови трансформації вітчизняної економіки. Обґрунтовано пріоритети діджиталізації бухгалтерського обліку. Наголошено, що пріоритетним напрямом модернізації бухгалтерського обліку є програмне забезпечення з елементами штучного інтелекту. Наведено приклади застосування технології блокчейн – розподіленої бази даних, яка слугує бухгалтерською книгою для операцій із криптовалютою. Визначені основні напрями державної підтримки, яка необхідна для швидкої трансформації економіки. Запропоновані подальші напрями вітчизняної економіки до економіки знань. RU: В исследовании рассмотрены исторические аспекты теории инновационной экономики и этапы ее современной трансформации. Освещены объективные и субъективные предпосылки перехода от индустриальной экономики к экономике знаний. Проанализировано понятие роли, места и характера функционирования знаний. Отмечено, что знания являются наиболее важным и определяющим фактором современной экономики. Выделены основные условия трансформации отечественной экономики. Обоснованы приоритеты диджитализации бухгалтерского учета. Отмечено, что приоритетным направлением модернизации бухгалтерского учета является программное обеспечение с элементами искусственного интеллекта. Приведены примеры применения технологии блокчейн – распределенной базы данных, которая служит бухгалтерской книгой для операций с криптовалютой. Определены основные направления государственной поддержки, которая необходима для быстрой трансформации экономики. Предложены дальнейшие направления трансформации отечественной экономики к экономике знаний. EN: The rapid development of digital technologies is manifested in the strengthening of information provision in the economy and management, as well as in the constant diversification of the information sector, which in turn requires an increase in knowledge. The domestic economy is increasingly facing the issue of modernization of information technologies and comprehensive digitalization. The purpose of this article is the theoretical basis and further prospects of accounting and analytical aspect of the transformation of the domestic economy in the light of global trends of Informatization of society. The study examines the historical aspects of the theory of innovation economy and the stages of its modern transformation. Objective and subjective of transition from industrial economy to knowledge economy are highlighted. The concept of the role, place and nature of knowledge functioning is analyzed. It is noted that knowledge is the most important and determining factor of the modern economy. The main conditions for the transformation of the domestic economy are highlighted. Priorities of digitalization of accounting are substantiated. It is noted that the priority direction of modernization of accounting is software with elements of artificial intelligence. Examples of the use of block chain technology as a distributed database, which serves as a register of transactions with crypto currency, are given. The main directions of the state support which is necessary for fast transformation of economy are defined. Further directions of transformation of domestic economy to knowledge economy are offered. According to the study, it is concluded that the transformation of the domestic economy should begin with the digitalization of all activities, but first of all, from accounting. In accounting and analytical work at enterprises it is necessary to use the most modern software products, which will be based on elements of artificial intelligence. It is necessary to develop Blockchain technology as the most secure and transparent. But all this is not possible without state support. Only the interaction between the state, enterprises and scientific institutions can become a decisive factor in the formation of the future economy.
Transformation of the domestic economy: accounting and analytical aspect
Keywords: економіка; інновації; інформація; облік; аналіз; діджиталізація; блокчейн; криптовалюта; экономика; инновации; знания; информация; учет; анализ; диджитализация; еconomics; innovation; knowledge; information; accounting; analysis; digitalization; Blockchain; crypto currency